Occurrence of Arcellidae (Amorphea, Arcellinida) in a coastal stream in the State of Rio de Janeiro - Miranda, Viviane Bernardes dos Santos; Mantovano, Tatiane; Silva , Yemna Gomes da; Lansac-Tôha , Fábio Amodêo; Mazzoni, Rosana (Acta Scientiarum. Biological Sciences, 2020)
The aim of this study was to elaborate a taxonomic survey on the testate amoebae of the Family Arcellidae in coastal streams in the State of Rio de Janeiro. Six samplings were conducted in Ubatiba coastal stream (Maricá, RJ). In total, 130 liters water were filtered through a conical net of 60-μm mesh and preserved in 4% formalin. Organisms were identified with the aid of an inverted trinocular microscope. The morphological characteristics (lobose testate amoebae with shell composed of granular chitinoid elements) of each species were recorded. The species were described and illustrated. For the verification of new taxa records of Arcellidae in Rio de Janeiro and their distribution in Brazil, a search based on index articles by Scopus, Web of Science and Google Scholar using the keywords "tecamebas", "testate amoebae", "Arcella", "Arcellidae", "Brazil" and "Rio de Janeiro", was performed. Eight Arcellidae species were recorded. Some ecological and taxonomic information was provided. Due to the small amount of information on testate amoebae, this study is important because it reduces the knowledge gap regarding this community in the State of Rio de Janeiro. Furthermore, we suggest new studies on species identification to be conducted to expand regional knowledge about these organisms.